PENGARUH MEDIA PEMBELAJARAN AUDIOVISUAL TERHADAP HASIL BELAJAR SISWA UPT SPF SD INPRES PERUMNAS ANTANG III - Bili, Tresia Asna; Supardi, R.; Jusmawati, Jusmawati; Alam, Syamsul (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to determine the effect of audiovisual learning media on student learning outcomes at UPT SPF SD Inpres Perumnas Antang III. This research uses a quantitative approach with an experimental research design. The research sample consists of 28 students from class III A, selected using simple random sampling. The instruments used in this study include observation sheets, tests, and documentation. Descriptive analysis results show that student activity scored an average of 3.3, and teacher activity scored an average of 3.4, both categorized as "very good." Inferential analysis results show a normality test value of 0.095, a homogeneity test value of 0.069, and a t-test result of 0.001 < 0.05, which means H? is rejected. Therefore, it can be concluded that audiovisual learning media has an effect on student learning outcomes at UPT SPF SD Inpres Perumnas Antang III.